Best Answer

2x + (10x - 4) = 20 2x + 10x - 4 = 20 12x - 4 = 20 12x = 24 x = 2

Q: What is x in the problem 2x plus 10x - 4 equals 20?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

10x - 18 = 5x + 2 Add -5x + 18 to both sides of the equation, to get: 5x = 20, from which x = 4.

-20 = -4x - 6x -20 = -10x -20 / -10 = -10x / -10 2 = x x = 2

It is: -5x-20 when simplified

The given terms can be simplified to: 20x+20

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

Related questions

Depends on the value of x if x is 1 then 10x + 20 = 30 if x is 2 then 10x + 20 = 40 if x is 3 then 10x + 20 = 50 if x is 4 then 10x + 20 = 60 if x is 5 then 10x + 20 = 70 if x is 10 then 10x + 20 = 120 And so on

x + 20 + 10x = 20 + 9x 11x + 20 = 20 + 9x Subtract 20 from both sides: 11x = 9x Subtract 9x from both sides: 2x = 0 Divide both sides by 2: x = 0

If you mean:0 = 800 - 10x + 25 * 20 = 800-10x+25*210x = 800+50x = 8,50 = 800 - 10x + 25 * x * 20 = 800 - 10x + 50x-800 = 40x-50 = x

12x-3=2x+17 10x-3=17 10x=20 x=2

Calculate 10^2 - 4*(-16)*(-20)

10x - 18 = 5x + 2 Add -5x + 18 to both sides of the equation, to get: 5x = 20, from which x = 4.

98 - 3x = 10x + 20, solve for x.subtract 98 from both sides-3x = 10x - 78subtract 10x from both sides-13x = -78multiply both sides by -113 x = 78divide both sides by 13x = 6

-20 = -4x - 6x -20 = -10x -20 / -10 = -10x / -10 2 = x x = 2

Add 12 to each side: 4x + 6x = 20 ie 10x = 20 so x = 2

It is: -5x-20 when simplified

The given terms can be simplified to: 20x+20

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2